(untitled) (Research, Society and Development, 2020)
Dental materials are relatively rare to be swallowed, especially when it comes to orthodontic objects. However, this type of emergency can arise in the dental clinic environment. Although the ideal is to avoid its occurrence, it is necessary that the professional knows how to handle the situation, in cases that happen. Therefore, the aim of this article was to perform a literature review and describe a clinical case of ingestion of an orthodontic retainer. In this way, exemplify complications arising from accidental swallowing and propose possibilities of conduct. In order to obtain these answers, a literature review was carried out associated with a case study on the subject in question. As a result, it was found that the swallowing or aspiration of appliances or components associated with fixed or removable orthodontic appliances are the categories most cited in the literature. Regardless of the incidence, episodes such as ingestion or aspiration of a foreign body are recognized as possible complications in orthodontics. When accidents occur outside the dental office, patients are generally undergoing orthodontic treatment, which represents less than 10% of all cases of accidental swallowing. It is concluded that the investigation after the ingestion of any component of an orthodontic appliance is essential to ensure patient safety and to make any necessary medical referral for emergency care in order to avoid possible complications.